SISTEM PENDIDIKAN SURAU : KARAKTERISTIK, ISI, DAN LITERATUR KEAGAMAAN - MAS`UD ZEIN (Sosial Budaya, 2011)
Mosque constitutes eldest education institute at Minangkabau, even before input Islam goes to Minangkabau mosque have available. With its Islamic coming, mosque also experience islamisasi's process, without has to experience changing name. Hereafter mosque gets amends at Minangkabau. With its amends mosque education institute this, transformasi's happening scholarship and culture to Minang's young men. Knowledge that is gotten at this mosque not only theology just, but also knowledge which is needed deep life everyday, as gnostic as custom, self-defence knowledge, politeness, independence etcetera